Social Media and Its Impact on Bullying Behavior of Primary School Students - Haeroni, Ranita; Herwin; Adiwardana, Muh Rifqienur; Widyasari, Dexani (Universitas Pendidikan Ganesha, 2024)
The development of information technology, the internet and social media is increasingly changing the way of socializing. Social media contains various information that can access by all users without filters. This can trigger users to imitate what is presented on social media platforms, such as bullying behavior. This research aims to analyze the influence of social media on elementary school students' bullying behavior. The research method used is quantitative with survey research methods. The populations in this study were all fourth-grade elementary school students. The sampling in this study used a purposive sampling technique, namely fourth grade students consisting of 2 classes with a total of 37 students. The research instrument used a Likert scale type interval questionnaire. Data analysis techniques are descriptive tests, normality tests, linearity tests, and research hypothesis tests using simple linear regression tests. The results of this research show that social media has a significant influence on students' bullying behavior. This can be seen from the results of a simple linear regression test with a significant value of 0.000 < 0.05. Social media also has a strong influence on students' bullying behavior as shown by the correlation coefficient (R) of 0.816, this shows the degree of relationship between the social media variable (X) and bullying behavior (Y) of 81.6% which means social media has a strong influence on students' bullying behavior.